Using Reading Aloud and Question and Answer Technique in Improving Students' Ability in Reading Narrative Text at SMA Negeri 1 Ratahan Timur - Tini Mogea (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
This research is intended to prove whether reading aloud and question and answer techniques are effective or not in improving students’ ability to read narrative text at SMA Negeri 1 Ratahan Timur. This research is classified as classroom action research because it was conducted in a cycle. The second-grade students were taken as a sample consisting of 19 students. The writer used reflective journals, field notes, and tests in collecting data. The data were analyzed through the "triangulation" method. It is a kind of data analysis technique used to analyze qualitative data in which related data are compared and evaluated to explain the parallel characteristics. This was done to check whether the problem in reading comprehension of narrative texts has been overcome, all at once to check the student's progress. The result shows that by applying reading aloud in Cycle 1, It was found that only 36.84 % or 7 students of the 19 students could understand the text given with some comprehension and it was categorized as unsatisfying. The application of question and answer in Cycle 2, shows 52.63 % of 10 students made progress in the teaching-learning process of reading ability development and it was categorized as quite satisfying. By the combination of reading aloud and question and answer in Cycle 3 most of the students made great progress, with 68.42 % or 12 students, and it was categorized as satisfying.